2018
DOI: 10.1159/000487426
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Implementing 100% Rapid Review as a Quality Control Tool in Cervical Cytology

Abstract: Objective: We aimed to evaluate the impact of implementing 100% rapid review (100% RR) as a quality control tool in cervical smear cytology. Design: A cross-sectional study was conducted in which cytology findings, false-negative results, and quality indicators were evaluated. The variables were analyzed in 2004, the year in which 100% RR was implemented, and again in 2013, i.e., 10 years on. Results: Detection of atypical squamous cells of undetermined significance (ASC-US) increased from 0.90% in 2004 to 2.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
(15 reference statements)
0
5
1
Order By: Relevance
“…Compared with Magalhães et al [1] and Queiroz-Filho et al [2], our results after implementation of 100% rapid review showed significant increases in atypical squamous cells of undetermined significance; atypical squamous cells cannot exclude the categories of high-grade and low-grade squamous intraepithelial lesions.…”
contrasting
confidence: 85%
See 3 more Smart Citations
“…Compared with Magalhães et al [1] and Queiroz-Filho et al [2], our results after implementation of 100% rapid review showed significant increases in atypical squamous cells of undetermined significance; atypical squamous cells cannot exclude the categories of high-grade and low-grade squamous intraepithelial lesions.…”
contrasting
confidence: 85%
“…In quality control programs regarding cervical cytology, one goal is to reduce the number of false-negative results [1, 3]. Thus, despite the few differences between our study and the previous published studies, we may assume that 100% rapid review is an important tool to improve the effectiveness of screening programs.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…Of these, 8 were reclassified as ASC-H, and 2 were classified as HSIL. The type I laboratories classified 583 as positive smears, and the type II laboratory review reclassified 42 FP that had been previously classified as ASC-US (27), LSIL (1), ASC-H (5), HSIL (1), and AGC (8). All were reclassified as negative.…”
Section: Resultsmentioning
confidence: 99%